From Language Shift to Language Revitalization and Sustainability: A Complexity Approach to Linguistic Ecology - Comellas, Pere (Ecolinguística: Revista brasileira de ecologia e linguagem (ECO-REBEL), 2021)
Bastardas-Boada, Albert. From Language Shift to Language Revitalization and Sustainability: A Complexity Approach to Linguistic Ecology. Barcelona: Universitat de Barcelona, 2019.